Physico-chemical changes during growth and development of guava (Psidium guajava L.) fruits - Abdelgader, Sohad H.; Abu-Goukh, Abu-Bakr A.; Ali, Misson B. (Gezira Journal of Agricultural Science, 2023)
The aim of this study was to evaluate the physico-chemical changes during growth and development of ‘Shendi’ (pink-flesh) and ‘Pakistani’ (white-flesh) guava fruits, to provide base-line information regarding the biochemistry of the developing fruit to assist in determining harvest maturity of guava fruits. Twenty trees were selected from each cultivar in the Horticultural field, University of Khartoum farm at Shambat, Khartoum State. At time of flowering, the newly open flowers were tagged and fruit samples were harvested at different stages of growth and development. The first sample was picked four weeks after anthesis, and sampling continued every two weeks up to the over-ripe stage (6 samples). Forty fruits (10 fruits per replication) of uniform size and free of blemishes were picked at the designated stage, washed, air dried and arranged in a completely randomize design with four replications. Physical and chemical changes were determined using standard methods. The fruits of both cultivars followed a typical sigmoid curve. Fruit fresh weight, volume, length and diameter progressively increased from 4 weeks after anthesis up to 10 WAA, at physiological maturity, and then remained constant. Fresh weight increased from 12.1 g and 14.5 g at 4 WAA to 95.2 g and 107.1 g at physiological maturity (10 WAA) in ‘Shendi’ and ‘Pakistani’ cultivars, respectively. The white and pink guavas exhibited a typical climacteric pattern of respiration. Respiration rate was decreased from 85.6 and 69.9 mg CO₂/kg-hr (4 WAA) to 39.7 and 29.6 mg CO₂/kg-hr at physiological maturity (10 WAA), increased to 48.5 and 37.1 mg CO₂/kg-hr at the ripe stage (12 WAA), and dropped afterwards to 29.6 and 20.1 mg CO₂/kg-hr at the over-ripe stage (14 WAA) in ‘Shendi’ and ‘Pakistani’ fruits, respectively. Total sugars steadily increased on average, from 4.1 g/100 g (4 WAA) to 12.4 g/100 g (14 WAA). Ascorbic acid increased on average, from 19.9 mg/100 g (4 WAA), reaching a peak of 87.5 mg/100 g at physiological maturity and then decreased to 71.4 mg/100 g at the over-ripe stage. Phenolic compounds steadily decreased during growth and development from an average of 0.81 g/100 g at 4 WAA to 0.15 g/100 g at 14 WAA. The white-fleshed guavas had higher levels of total sugars, phenolic compounds, and ascorbic acid content, compared to the pink-fleshed fruits . It was recommended that guava fruits should be picked at physiological maturity (10 WAA), where the fruit size, fresh weight and volume are at their maximum values, respiration rate at the minimum level, total and reducing sugars are high, ascorbic acid content at maximum level and phenolic compounds are reasonably low.